Management and leadership in nursing and health care : an experiential approach - Rigolosi, Elaine La Monica, 1944- (Springer, 2013)
Time-tested leadership and management strategies based on experiential learning activities are at the foundation of this text for undergraduate and graduate students in nursing and health care leadership or management courses. It is grounded in theories and concepts applied to the health care environment from business, organizational psychology, health care law, and educational administration fields. The text encompasses theories of effective communication, problem analysis, conflict resolution, and time management challenges. This new edition includes three new chapters that cover current the.